2019
DOI: 10.1093/ehjci/jez049
|View full text |Cite
|
Sign up to set email alerts
|

Time course of left ventricular remodelling and mechanics after aortic valve surgery: aortic stenosis vs. aortic regurgitation

Abstract: Aims Pressure overload in aortic stenosis (AS) and both pressure and volume overload in aortic regurgitation (AR) induce concentric and eccentric hypertrophy, respectively. These structural changes influence left ventricular (LV) mechanics, but little is known about the time course of LV remodelling and mechanics after aortic valve surgery (AVR) and its differences in AS vs. AR. The present study aimed to characterize the time course of LV mass index (LVMI) and LV mechanics [by LV global long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…This may be partly explained by the load dependency of GLS, where an increase in SV and concomitant increase in EDV, as seen in AR, will have opposing effects on GLS [26,27]. The same observation was made by Vollema et al, who suggested that the finding was related to the Frank-Starling mechanism; hence, a reduction in preload will lead to a decrease in myocardial contraction force and consequently GLS [28]. The interaction between GLS and loading conditions was also evident in a study of 47 patients with AR undergoing valve surgery, in whom the absolute GLS decreased after surgery, whereas the normalized GLS calculated as the GLS/EDV ratio increased, primarily driven by a reduction in EDV after surgery [29].…”
Section: Systolic LV Functionmentioning
confidence: 68%
“…This may be partly explained by the load dependency of GLS, where an increase in SV and concomitant increase in EDV, as seen in AR, will have opposing effects on GLS [26,27]. The same observation was made by Vollema et al, who suggested that the finding was related to the Frank-Starling mechanism; hence, a reduction in preload will lead to a decrease in myocardial contraction force and consequently GLS [28]. The interaction between GLS and loading conditions was also evident in a study of 47 patients with AR undergoing valve surgery, in whom the absolute GLS decreased after surgery, whereas the normalized GLS calculated as the GLS/EDV ratio increased, primarily driven by a reduction in EDV after surgery [29].…”
Section: Systolic LV Functionmentioning
confidence: 68%
“…In our study, we followed-up our groups in 6.77±2.05 months. Despite the fact that LVMR after AVR appeared in both aortic stenosis and regurgitation cases [28], complete LVMR can be reached in a 2 and 5 year period, respectively. A similar trend was observed in our study, where the LVM of AS patients regressed better in the same follow-up time compared to AR patents.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, Une et al [ 21 ] showed that LV mass regression in both patients with aortic stenosis (AS) and those with aortic regurgitation (AR) occurred at a steep decline over 2 years after AVR. Vollema et al [ 22 ] reported that LV mass regression and changes in LV global longitudinal strain were similar despite different preoperative LV remodeling in patients with AS and those with AR. These findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%